Analisa dan Perancangan Sistem Informasi Perpustakaan Sekolah Berbasis Website di SMAN 1 NAGRAK - Rizky Gimnastiar; Muhlis; Indrawan; Ramadhana Eka Syahputra; Aries Saifudin (CV. Multi Kreasi Media, 2023)
The library system that runs at SMAN 1 NAGRAK, Sukabumi Regency uses a manual method, namely searching, checking and returning by hand writing. Books that students want to borrow are sometimes not available in the library. This has reduced the effectiveness and efficiency of library services. These problems require the system to be developed using the waterfall methodology, where the process is structured to ensure that the system is worthy. This system was created for research and development of a website-based library with PHP programming language and MySQL database. This information system is intended to help manage library member data, book data, borrowing, returning books and fines that have been equipped with reports that can be adjusted by users at SMAN 1 NAGRAK.